Penerapan Teknologi Tepat Guna Berbasis Energi Surya untuk Pengolahan Hasil Pertanian Menjadi Berbagai Produk Industri Rumah Tangga - Muhammad Hasim S., S.,; Iris Sumariyanto; Wahyudi Wahyudi; Akmal Hidayat; Mudarris Mudarris (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2024)
Indonesia as an agricultural country has great potential in processing agricultural products. However, most agricultural products are still processed into raw products with low economic value. Traditional processing of agricultural products into home industry products is inefficient, resulting in a lot of wasted crops. The solution to increase efficiency is to apply appropriate technology based on solar energy. Solar energy, as an environmentally friendly renewable energy source, can reduce the use of fossil fuels and greenhouse gas emissions, while increasing community income. The service shows that the application of appropriate technology for processing agricultural products into various solar energy-based home industry products is more efficient and meets quality standards. The benefits include economic improvement, environmental sustainability, and productivity optimization. The implementation method involves seven stages of community development from awareness to technology maintenance and development.